Trends in the use of video consultation in general practice during COVID-19: impact of practice and country characteristics based on the international, cross-sectional PRICOV-19 study - Ulrik Bak Kirk; Maria de la Cruz Gomez Pellin; Kathryn Hoffmann; Florian Odilo Stummer; Esther Van Poel; Claus Høstrup Vestergaard; Anne Holm; Athina Tatsioni; Ferdinando Petrazzuoli; Ana Luisa Neves; Raquel Gomez Bravo; Radost Asenova; et al. (BMC Primary Care)
Abstract Background The COVID-19 pandemic accelerated the use of telemedicine, specifically video consultations as they provide healthcare access in challenging situations where face-to-face encounters are not possible. Nevertheless, it remains largely unknown to what extent the organisation of general practice and national digital infrastructures have impacted the uptake and use of video consultations. Objective This study examined the variation in use of video consultations in general practice across Europe during the COVID-19 pandemic and explored associations with practice- and country-level characteristics. Methods This study is part of the international PRICOV-19 project, using data from an online survey and additional questions from national leads. First, we conducted a rapid literature search to support an evidence-based selection of the PRICOV-19 main survey items and additional questions aligned with our aims. Then, we included five practice-level and nine country-level characteristics, as well as COVID-19 intensity characteristics, as independent variables in the analysis. Finally, we conducted a linear mixed model analysis at the country-level, examining five models incrementally within a one-level random intercept regression model. Results Data from 5,065 general practices in 38 countries revealed that fewer than half (47.5%) utilized video consultations during the COVID-19 pandemic. Usage was highest in the United Kingdom, Luxembourg, Scandinavia, and France (82.6–94.4%) and the lowest in Portugal, Spain, Serbia, Bosnia and Herzegovina, Switzerland, and the Czech Republic (11.1–23.1%). At practice-level, key factors associated with higher usage included having more patients than average with a history of migration and difficulty speaking the local language, being a self-employed general practitioner, having a higher number of registered patients, and being urban-based. At country level, only accessible and affordable internet was statistically significantly associated with use of video consultations. Conclusions The study corroborates some established trends in telemedicine adoption while also providing new insights into specific practice-level factors that facilitated the use of video consultations in general practice across European countries during COVID-19. While some factors are universally influential, particularly internet access and affordability, others are more context-dependent. Trial registration Not applicable.